Integrated Open Loop Resonator Filter Designed with Notch Patch Antenna for Microwave Applications - D. Azra Awang Mat; N. Syuhada Hasim; Nurmiza Othman; Amira Amran; D. Norkhairunnisa Abang Zaidel; A. S. Wani Marzuki; Shafrida Sahrani; Kismet anak Hong Ping; Rohana Sapawi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This paper presented the design of integrated open loop resonator bandpass filter with notch type antenna for the use in microwave applications. Chebyshev type filter is selected as the filter characteristics and cascaded design with the antenna to produce a single module, Integrated Filter Antenna (IFA). Special feature of the antenna is the implementation of notch on the patch antenna to improve the efficiency. IFA is then simulated in electromagnetic simulation tool, Agilent Advance Design System (ADS) version 2016 and measured using R&S Vector Network Analyzer. It shows that the proposed IFA produced good measured return loss >-30dB with both vertical and horizontal gain of 9.11dBi and 8.01dBi respectively.